Who reads Tocqueville today? - Silva, Filipe Carreira da (2016)
In the 1960s and 1970s, Raymond Aron’s Main Currents of Sociological Thought introduced Tocqueville to a generation of sociologists alongside Weber, Durkheim and Marx. Granted, Tocqueville never made it to the inner circle of the sociological canon (that was reserved for the Marx-Durkheim-Weber trio), but Democracy in America was generally acknowledged as a classic in political sociology and some of the most important sociological works of American sociology in the 1960s were Tocquevillian in character. Think of Martin Seymour Lipset’s Political Man (1960), or Reinhardt Bendix’s Nation-Building and Citizenship (1964). The late 1960s mark the peak of Tocqueville’s prestige in sociology. From that point onwards, Tocqueville’s influence and prestige among sociologists begins to decline in such a way that today he is barely mentioned in sociology classrooms. This brings me to the issue I wish to tackle in this paper. Why is Tocqueville dead in sociology today?